2021
DOI: 10.3389/fendo.2021.706352
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Perfluoroalkyl Chemicals and Cardiovascular Disease: Experimental and Epidemiological Evidence

Abstract: Polyfluoro- and perfluoro–alkyl substances (PFAS) are organic chemicals extensively used worldwide for industry and consumer products. Due to their chemical stability, PFAS represent a major cause of environmental pollution. PFAS accumulate in animal and human blood and tissues exerting their toxicity. We performed a review of the epidemiological studies exploring the relationship between exposure to PFAS and thromboembolic cardiovascular disease. An increase in cardiovascular disease or death related to PFAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 81 publications
1
37
0
Order By: Relevance
“…There is also increasing experimental evidence linking PFAS exposure to platelet activation and thrombus formation. 11 Our observed associations with arrhythmias have not been previously examined and may suggest a novel cardiac parameter worthy of further investigation. Outside of these individual chronic diseases, we also observed associations with osteoporosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…There is also increasing experimental evidence linking PFAS exposure to platelet activation and thrombus formation. 11 Our observed associations with arrhythmias have not been previously examined and may suggest a novel cardiac parameter worthy of further investigation. Outside of these individual chronic diseases, we also observed associations with osteoporosis.…”
Section: Discussionmentioning
confidence: 79%
“…airborne dust, food packaging, and cookware may all remain relevant to this day. 4 PFAS exposure is associated with multiple health outcomes including cancer, 5 lipid metabolism, 6 , 7 thyroid disruption, 8 , 9 cardiovascular disease, 10 , 11 and kidney disease. 12 , 13 In addition, mechanistic studies have probed the molecular actions that lead to such a wide array of health outcomes for PFAS and have shown that PFAS are associated with increases in markers of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…PFAS are exclusively man-made EDCs and environmentally persistent chemicals which are used to manufacture a wide variety of consumer and industrial products, non-stick, stain and water resistant coatings, fire suppression foams, and cleaning products (Liu et al (2018) and Jain and Ducatman (2018)). Both PFAS and metals have been associated with increase in cardiovascular disease (CVD) or death using many cross-sectional and longitudinal observational studies and experimental animal models (Meneguzzi et al (2021)). Hypercholesterolemia is one of the significant risk factors for CVD and it is characterized by the presence of high levels of cholesterol in the blood.…”
Section: Application In Exposure-mixture Association Of Per-and Poly-...mentioning
confidence: 99%
“…4 Application in exposure-mixture association of PFAS and metals with serum lipids among US adults PFAS are exclusively man-made EDCs and environmentally persistent chemicals which are used to manufacture a wide variety of consumer and industrial products, non-stick, stain and water resistant coatings, fire suppression foams, and cleaning products (Liu et al (2018) and Jain and Ducatman (2018)). Both PFAS and metals have been associated with increase in cardiovascular disease (CVD) or death using many crosssectional and longitudinal observational studies and experimental animal models (Meneguzzi et al (2021)).…”
Section: Notion Of Sufficient Sample Sizementioning
confidence: 99%
“…A common thread linking these diseases is a change in hemodynamics connected to ischemic injury [180][181][182], a factor that independently drives LUTD in mice [174]. Environmental chemical exposures have been linked to cardiovascular disease and diabetes [183][184][185][186], and this is another mechanism by which they may drive LUTD.…”
Section: The Relationship Between Lutd and Comorbiditiesmentioning
confidence: 99%